Existence and computation of pure-strategy equilibria in models of legislative bargaining with reconsideration - Daniel Diermeier; Pohan Fong (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2008)
Diermeier and Fong (2008a) recently proposed a legislative bargaining model with reconsideration in the context of a distributive policy environment. In this paper we prove general existence and necessary conditions for pure-strategy stationary equilibria for any finite policy space and preference profile. We also provide an algorithm to compute these equilibria. In any such equilibrium proposal power is endogenously limited compared to the case of no reconsideration. The general model is then applied to various policy environments, including a model with spatial preferences. In the context of a public goods environment we can show that lack of commitment increases policy efficiency.
Keywords: C72; D72; D78; 330; Legislative bargaining; reconsideration; evolving default; proposal power; lack of commitment; distributive politics; public goods; spatial model